2017
DOI: 10.3389/fmicb.2017.00550
|View full text |Cite
|
Sign up to set email alerts
|

Reveromycins A and B from Streptomyces sp. 3–10: Antifungal Activity against Plant Pathogenic Fungi In vitro and in a Strawberry Food Model System

Abstract: This study was conducted to determine the antifungal activity of the metabolites from Streptomyces sp. 3–10, and to purify and identify the metabolites. Meanwhile, the taxonomic status of strain 3–10 was re-evaluated. The cultural filtrates of strain 3–10 in potato dextrose broth were extracted with ethyl acetate. The resulting crude extract at 1 and 5 μg/ml inhibited growth of 22 species in 18 genera of plant pathogenic fungi and Oomycetes, accounting for 92% of the total 24 tested species, suggesting that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Two compounds were purified from Streptomyces sp. 3-10, and were identified as reveromycins A and B, which demonstrated high antifungal activity against Botrytis cinerea, Mucor hiemalis, Rhizopus stolonifer , and Sclerotinia sclerotiorum (Lyu et al, 2017 ). Srivastava et al found Chrestomyceticus could produce metabolites with antifungal activity against Candida albicans (Srivastava and Dubey, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two compounds were purified from Streptomyces sp. 3-10, and were identified as reveromycins A and B, which demonstrated high antifungal activity against Botrytis cinerea, Mucor hiemalis, Rhizopus stolonifer , and Sclerotinia sclerotiorum (Lyu et al, 2017 ). Srivastava et al found Chrestomyceticus could produce metabolites with antifungal activity against Candida albicans (Srivastava and Dubey, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…(Ser et al, 2016 ). Streptomyces species are Gram-positive, filamentous, and sporulating actinobacteria, with a high G + C content in their genomes (Lyu et al, 2017 ). They exhibit an immense biocontrol activity against a range of phytopathogens (Wang X. N. et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many Streptomyces species have been successfully evaluated as biocontrol agents against phytopathogens ( Berg et al, 2001 ; Minuto et al, 2006 ; Law et al, 2017 ). Some antibiotic compounds ( Al-Bari et al, 2007 ; Zucchi et al, 2008 ; Lyu et al, 2017 ) and other compounds such as chitinases ( Gomes et al, 2001 ; Mander et al, 2016 ) produced by Streptomyces spp. have a strong antagonistic effect on growth and development of Aspergillus .…”
Section: Introductionmentioning
confidence: 99%
“…Low antifungal activity was observed for the Nystatin. Previous studies also show differential activities of various antifungals against the fungal isolates recovered from various foods [23,30].…”
Section: Discussionmentioning
confidence: 88%